Numerical modeling for the evaluation of grout penetration in fractured rock masses - Y. Mito, Y. Mito; M. Ashraf, M. Ashraf; T. Yamamoto, T. Yamamoto (2011)
Grouting aims to reduce the permeability of rock mass below the required value and has been widely used in rock engineering field for a long time.